Algumas possibilidades estéticas decorrentes da utilização de equipamento fotográfico digital: documentário fotográfico do analógico ao digital - Andre Ribeiro de Salles Coelho (2006)
A reflexion about the artistic possiblities on photography captioning of images by using analogical and digital resources. This dissertation is composed by a photographic work with texts and examples of the main subjects of the new ways of the photographic doing, accompanied withphotos and descriptions of the used techniques. The photographic works theme was the guardas de congado, moçambique e folia de reis of Aparecida square, a neighbourhood situated in the city of Belo Horizonte. During the work, I could research and utilize the artistic possibilities that the digital resources allow, such as equipment versatility, velocity andilumination possibilities and the low cost of development and loading of the photographs called digitals.